(untitled) (Docentes 2.0 Journal, 2025)
The evolution of higher education has transformed teaching, requiring online professors to update their transversal skills. The objective of this research was to characterize professors’ perceptions of these skills at the Open and Distance University (Universidad Abierta y a Distancia), one of the leading distance education institutions in Latin America. The study was framed within the positivist paradigm, using a deductive method, a quantitative approach, and a non-experimental, descriptive, cross-sectional design. An online questionnaire, adapted from the Tuning project, was administered to a sample of 703 professors. The data were analyzed using descriptive statistics in SPSS. The findings reveal a heterogeneous perception: while professors value their interpersonal and methodological skills highly, a significant gap was identified in their technological competencies. The lowest score in this area corresponded to the advanced use of ICT tools, which was identified as a critical area for improvement. Furthermore, the results suggest a perceived lack of professional knowledge, a finding linked to insufficient time dedicated to continuing education. The study highlights that, to ensure the quality of online education, institutions need to strengthen their faculty’s digital skills and professional development. It also points to the need to design development programs to optimize the use of technology and improve pedagogical management, key elements for educational success.